HUBUNGAN DURASI PENGGUNAAN DAN POSTUR PENGGUNA SMARTPHONE TERHADAP RISIKO NYERI PERGELANGAN TANGAN PADA MAHASISWA AKTIF FAKULTAS KEDOKTERAN UPN VETERAN JAKARTA TAHUN 2022 - Arda Maghfira Qathrunnada, (2022)
Background: Online learning organized by universities due to the impact of the Covid-19 outbreak. The use of mobile technology such as smartphones supports the achievement of distance learning goals. Increased use of smartphones can increase health risks such as wrist pain. This is due to the repeated use of the thumb, abnormal use and dominance when typing when its compared to the use of the thumb when using a laptop or computer which is normally only type spaces. Methods: This research is a cross sectional study on 111 respondents using a questionnaire and measuring posture using RULA. Data were analyzed using chi square test. Results: Most respondents had a low-risk sitting posture (score 3-4), sat using a smartphone for more than or equal to 4 hours a day, and used a smartphone with a screen size of 4-7 inches. Based on the results of data analysis, it was found that there was an effect of duration of use with wrist pain with a p value of 0.000 (p <0.05) and no effect of user's posture with wrist pain. Conclusion: Duration of use can affect Wrist Pain. Respondents had to pay attention to the duration of smartphone use and rest and stretch for 10 minutes each time using a smartphone for 2 hours.